Learning by Doing vs Learning by Researching in a Model of Climate Change Policy Analysis - Marzio Galeotti; Sergio Vergalli; Efrem Castelnuovo; Gretel Gambarelli (Fondazione Eni Enrico Mattei (FEEM), 2003)
Many predictions and conclusions in climate change literature have been made on the basis of theoretical analyses and quantitative models that assume exogenous technological change. One may wonder if those policy prescriptions hold in the more realistic case of endogenously evolving technologies. In previous work we modified a popular integrated assessment model to allow for an explicit role of the stock of knowledge which accumulates through R&D investment. In our formulation knowledge affects the output production technology and the emission-output ratio. In this paper we make progress in our efforts aimed to model the process of technological change. In keeping with recent theories of endogenous growth, we specify two ways in which knowledge accumulates: via a deliberate, optimally selected R&D decision or via experience, giving rise to Learning by Doing. We simulate the model under the two versions of endogenous technical change and look at the dynamics of a number of relevant variables.
Keywords: H0; H2; H3; 330; Climate Policy; Environmental Modeling; Integrated Assessment; Technical Change; Klimawandel; Klimaschutz; Umweltbewertung; Technischer Fortschritt; Forschung; Lernprozess; Theorie; Welt